2021
DOI: 10.1111/ijfs.14945
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion‐forming properties of heat‐induced pork myofibrillar protein affected by NaCl

Abstract: Summary The emulsification characteristics of myofibrillar proteins (MPs) with different NaCl concentrations also affect the quality of meat products after cooking. We investigated the effects of heating (100 °C) on the solubility, emulsifying activity, and conformational and environmental changes of MPs prepared with different NaCl concentrations. Emulsifying activity increased with increasing NaCl prior to heating, but there was no significant effect after heating. The viscosity increased and particle size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…At an identical shear rate, the viscosity of 2.0 % fat addition was the highest. Earlier studies demonstrated that higher emulsion viscosity reduces protein aggregate formation, slows emulsion particle settlement or aggregation, and thus enhances emulsion stability ( Zhu et al, 2021 ). Additionally, increasing viscosity can slow oil droplet movement in the emulsion, lessen oil droplet collisions, and improve emulsion stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At an identical shear rate, the viscosity of 2.0 % fat addition was the highest. Earlier studies demonstrated that higher emulsion viscosity reduces protein aggregate formation, slows emulsion particle settlement or aggregation, and thus enhances emulsion stability ( Zhu et al, 2021 ). Additionally, increasing viscosity can slow oil droplet movement in the emulsion, lessen oil droplet collisions, and improve emulsion stability.…”
Section: Resultsmentioning
confidence: 99%
“…With 2.5 % fat addition, viscosity decreased, possibly because excessive fat hindered chicken soup emulsification, leading to larger particle creation ( Zou, Xu, Zou, & Yang, 2021 ). Research also suggested soup viscosity could be influenced by particle size and interactions, with finer particles disperse better in soup, resulting in higher viscosities ( Zhu et al, 2021 ). These outcomes align with this study's microscopic imaging findings.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with particle size measurement results (Table 1). As the temperature was increased, the protein gradually denatured, the hydrogen bonds and other hydrophobic bonds that maintain the protein structure were broken, the secondary and the tertiary structure as well as the moisture content of the protein gel was lost, and therefore the hardness was increased (Promeyrat et al., 2011; Zhu et al., 2021). Sun and Arntfield (2011) previously found that at temperatures exceeding the myosin denaturation temperature, the molecules start to expose their reactive groups, leading to cross‐linking and an eventual increase in the hardness of the gel.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with particle size measurement results (Table 1). As the temperature was increased, the protein gradually denatured, the hydrogen TA B L E 1 Effect of temperature (56 and 72℃) and NaCl on particle size (nm) of pork myofibrillar protein bonds and other hydrophobic bonds that maintain the protein structure were broken, the secondary and the tertiary structure as well as the moisture content of the protein gel was lost, and therefore the hardness was increased (Promeyrat et al, 2011;Zhu et al, 2021).…”
Section: Texturementioning
confidence: 99%
“…In addition to being an essential ingredient in meat products to maintain good flavor, texture, and shelf life, NaCl is also an essential auxiliary in meat processing [ 9 ]. Being a salt-soluble protein, the functional properties of MP are influenced by many environmental factors including ionic strength [ 10 ].…”
Section: Introductionmentioning
confidence: 99%